2020
DOI: 10.4314/ejhs.v30i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Community-Based Healthcare Insurance Schemes in Developing Countries: A Case of Lahore, Pakistan

Abstract: BACKGROUND: Healthcare costs and poverty are significant barriers to achieving universal access to healthcare. Thus, Community-Based Health Insurance Schemes (CBHIS) are regarded as an influential instrument for providing access to healthcare. For this purpose, this study was carried out in order to assess the community’s Willingness to Pay (WTP) for CBHIS and its determinants among the residents of Lahore City.METHODS: A cross-sectional study was adopted during the period of May 2018 to August 2018 to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Those individuals who had high monthly income were more likely to pay for the CBHI scheme than those who had low monthly income (less than 500ETB). This finding is similar with studies done in Malaysia [ 53 ], India [ 54 ], Pakistan [ 38 ], Bangladesh [ 37 ], Cameron [ 51 ], and Sierra Leone [ 55 ]. This could be because respondents with high income might have enough resources to pay for the requested CBHI scheme premium to protect their family members from unpredictable illnesses [ 24 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Those individuals who had high monthly income were more likely to pay for the CBHI scheme than those who had low monthly income (less than 500ETB). This finding is similar with studies done in Malaysia [ 53 ], India [ 54 ], Pakistan [ 38 ], Bangladesh [ 37 ], Cameron [ 51 ], and Sierra Leone [ 55 ]. This could be because respondents with high income might have enough resources to pay for the requested CBHI scheme premium to protect their family members from unpredictable illnesses [ 24 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar with studies done in Malaysia [ 53 ], India [ 54 ], Pakistan [ 38 ], Bangladesh [ 37 ], Cameron [ 51 ], and Sierra Leone [ 55 ]. This could be because respondents with high income might have enough resources to pay for the requested CBHI scheme premium to protect their family members from unpredictable illnesses [ 24 , 38 ]. We found that the distance respondents reside from the public facility had a significant effect on WTP for the CBHI scheme.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this connection, many investigators have carried out studies to investigate the factors that influence healthcare expenditure within the particular nations. Cantarero, Prieto, David, and Santiago (Sana et al, 2020) as well as (Lord et al, 2020) all examined this notion further in their own research. However, other researchers have used cross-national data to investigate what factors influence health care costs.…”
Section: Socioeconomic Profile Of Pakistanmentioning
confidence: 99%
“…In short, Pakistan's health care system is a highly unequal, western-oriented curative care paradigm that fails to meet needs of an overwhelming majority of Pakistanis (Zaidi). Pakistan has done well on several health measures, its recital is not up to standard when compared to that of its South Asian neighbors (Sana et al, 2020). Health is regarded as integral part of human capital and investment in health is regarded as basic human right and which will end in improved human life.…”
Section: Socioeconomic Profile Of Pakistanmentioning
confidence: 99%